1997
DOI: 10.1023/a:1005855318665
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to compare different bacteriological aspects of the respiratory systems of healthy (H) versus unhealthy (UH) animals with respiratory signs. The prevalence of different bacterial species was determined in the upper and lower respiratory tract of H and UH Najdi sheep, Somali sheep and Holstein calves. The characteristics of Pasteurella spp. isolates, and the biotype of Pasteurella haemolytica were identified in H and UH animals, Eighteen out of 28 (64.3%) of the identified bacterial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Trueperella pyogenes is a common bacterial isolate from chronic suppurative pneumonia in cattle [15,20], and sheep [21]. Extended treatment with procaine penicillin in this study was effective where lung lesions did not extend dorsally more than 10 to 15 cm above the level on the chest wall indicated by the point of the olecranon however no long term survival data are available as culling was recommended because of the likelihood of recurrence following stress (e.g.…”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Trueperella pyogenes is a common bacterial isolate from chronic suppurative pneumonia in cattle [15,20], and sheep [21]. Extended treatment with procaine penicillin in this study was effective where lung lesions did not extend dorsally more than 10 to 15 cm above the level on the chest wall indicated by the point of the olecranon however no long term survival data are available as culling was recommended because of the likelihood of recurrence following stress (e.g.…”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Previously, the bacteria in healthy domestic sheep lungs had been investigated by culture-based methods, which seemed to indicate that bacterial colonization of the sheep lung was rare or did not occur in all sheep ( 11 , 12 , 14 ). In contrast, using non-culture-based methods, we have found that all of the sampled sites in our seven sheep harbored diverse communities of bacteria, although in far smaller numbers than is generally found in other niches, such as the gut or upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…The lung microbiota of healthy domestic sheep has previously been investigated using culture-based methods ( 11 14 ), but these studies have shown conflicting descriptions of the extent of lung colonization by bacteria. A study of pneumonic Bighorn sheep lungs found that, for most sheep studied, bacterial 16S rRNA gene amplification and sequencing was able to identify additional bacterial species which were not found by culturing ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success was defined as a rapid return to normal appetite, marked improvement in body condition, and normal respiratory rate. Penicillin is the antibiotic of choice for chronic respiratory disease in cattle and sheep because of the frequent isolation of Arcanobacterium pyogenes [11, 18]. Arcanobacterium pyogenes was the most common bacterial isolate from chronic suppurative pneumonia cases in cattle and such chronic infections were treated with a 4–6-week course of procaine penicillin with reasonable success [8].…”
Section: Discussionmentioning
confidence: 99%